Konsep Pendidikan Islam Dalam Al-Qur’an Surat Lukman - Rois, Ajun (Ikatan Da'i Indonesia, 2022)
This qualitative research with the aim of: 1) To know understanding, the principles of Islamic education methods and materials about the concept of Islamic education 2) To express a review of the concept of Islamic education, the sources of study based on Al-Qur'an and As-Sunah are both is a guide for Muslims to reach mardlotillah (Ridho Allah). The research uses a qualitative approach of type of literature research method (Librari Research) and the steps taken are 1) Reviewing the books of science education, Islamic education, the books relevant to the discussion 2) Sorting (reduction) 3) Data grouping 4) Check the validity of the data. The process of data interpretation is done after the examination phase of the data. Interpretation of data and writing of research results by using inductive descriptive analysis. Based on document analysis, the research results show that the authors prepare the materials to be discussed from the books and books relevant to the issues to be discussed, both primary and secondary. Primary sources are books or books that deal with education, both in general education and religious education. The secondary sources are books or books that do not specifically address education but have something to do with the discussion. That Islam is a plenary religion that regulates all aspects of human life including in it religious education in children should follow the concepts that are shown by Allah and His Messenger that is through the holy book (Al-Qur'an) and the Sunnah of His Apostle, in this case means making the Messenger of Allah as the ideal model in an effort to realize the concepts that exist in the Qur'an. Although the Qur'an and As-Sunna have been so firmly obliged to follow it but still there are among Muslim parents who have not made the Qur'an and As-Sunah as a guide in educating their children. Problems arise how our efforts to the concept of Islamic education must be implemented in accordance with the teachings of Islam.